2012
DOI: 10.1074/jbc.m111.275610
|View full text |Cite
|
Sign up to set email alerts
|

Scleraxis Modulates Bone Morphogenetic Protein 4 (BMP4)-Smad1 Protein-Smooth Muscle α-Actin (SMA) Signal Transduction in Diabetic Nephropathy

Abstract: Background: Activated mesangial cells exhibit SMA and contribute to the progression of diabetic nephropathy. Results: Scleraxis negatively regulated the AGE-induced expression and secretion of BMP4. Conclusion: Scleraxis and Id1 are involved in the BMP4-SMA pathway and modulate phenotypic changes. Significance: Deeper insight into the impact of regulatory mechanism of scleraxis-BMP4-Smad1 signal activation might help to prevent diabetic glomerular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 60 publications
(36 reference statements)
2
18
1
Order By: Relevance
“…In support of this conclusion, it was recently reported that E2F1 plays a tumor suppressor role in colorectal cancer by activating CTNNBIP1 and inhibiting β-catenin activity [37]. MC activation, which is characterized by the induction of α-SMA expression, contributes to diabetic renal diseases [59]. Our results also demonstrate that transcriptionally active β-catenin induces α-SMA expression, which is indicative of MC activation and is accompanied by increased fibronectin expression in MMCs that are transfected with CTNNBIP1 siRNA and/or an miR-215 mimic.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In support of this conclusion, it was recently reported that E2F1 plays a tumor suppressor role in colorectal cancer by activating CTNNBIP1 and inhibiting β-catenin activity [37]. MC activation, which is characterized by the induction of α-SMA expression, contributes to diabetic renal diseases [59]. Our results also demonstrate that transcriptionally active β-catenin induces α-SMA expression, which is indicative of MC activation and is accompanied by increased fibronectin expression in MMCs that are transfected with CTNNBIP1 siRNA and/or an miR-215 mimic.…”
Section: Discussionmentioning
confidence: 72%
“…Gene annotations demonstrated that CTNNBIP1 prevented the interaction between β-catenin and TCF/LEF family members, thus acting as a negative regulator of the Wnt/β-catenin signaling pathway [35], [55]-[58]. The central effector of the canonical Wnt cascade is β-catenin, which binds to TCF or LEF to initiate Wnt target gene transcription, including the myofibroblast conversion marker α-SMA and the fibrotic matrix protein fibronectin [47], [59], [60]. Additionally, using both gain- and loss-of-function experiments, we determined that only miR-215 regulated endogenous CTNNBIP1 expression ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Scx can also directly transactivate the Twist1 and Snai1 promoters, 2 transcriptional regulators of epithelial mesenchymal transition, further suggesting that Scx can drive myofibroblast differentiation in cardiac fibroblasts (27). However, the effects of Scx-induced aSMA expression are tissue specific as it has previously been shown that Scx represses aSMA expression in the mesangial cells of the kidney (28). In our flexor tendon repair model, we found that a subset of Scx Lin differentiated into myofibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the expression of scleraxis [33][34][35], Nanog [36], and Sox 2 [37] in the cytoplasm. Although these transcription factors function in the cell nucleus, stimulatory signal is likely required to induce their translocation to the cell nucleus.…”
Section: Role Of Lrcs During Tendon Repairmentioning
confidence: 95%